THE USE OF PROJECT METHODS IN TEACHING A FOREIGN LANGUAGE: THEORY, PRACTICE, AND INNOVATION (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the methodological and pedagogical potential of the project method as an effective tool for teaching foreign languages in modern education. The study explores the theoretical underpinnings of the project-based approach, its influence on developing communicative competence, creativity, and critical thinking, and its integration within blended and digital learning environments. Emphasis is placed on the project method’s role in enhancing student motivation, intercultural competence, and learner autonomy. The article also analyzes practical models of applying project-based learning (PBL) in linguistic and non-linguistic universities, highlighting its adaptability to professional and cultural contexts. Ultimately, project-based learning is viewed as a key mechanism for aligning foreign language education with 21st-century pedagogical standards.